PENGARUH SOCIAL MEDIA MARKETING, DIGITAL PERIKLANAN, DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PENGGUNA LAYANAN MAXIM - Nopi Fitri; Lukmanul Hakim (ITB AAS Indonesia Surakarta, 2026)
This study aimed to analyze the effect of social media marketing, digital advertising, and online customer reviews on user decisions of Maxim ride-hailing services. Digital transformation in marketing has encouraged companies to optimize technology-based promotional strategies to influence consumer decisions. The research used a quantitative approach with a survey method. Data were collected through questionnaires distributed to Maxim users in Bandar Lampung. SmartPLS was applied. The results showed that partially social media marketing, digital advertising, and online customer reviews had significant effects on user decisions. Simultaneously, the three independent variables significantly affected user decisions. Keywords: Social Media Marketing; Digital Advertising; Online customer review; User Decision; Maxim